Enhanced production of d‐psicose 3‐epimerase in Bacillus subtilis by regulation of segmented fermentation. (29th October 2019) - Fu, Gang; Zhang, Shibin; Dong, Huina; Chen, Jingqi; Tu, Ran; Zhang, Dawei
Abstract: d ‐Psicose 3‐epimerase is an enzyme that catalyzes the synthesis of d ‐psicose from d ‐fructose. We cloned the d ‐psicose 3‐epimerase from Ruminococcus sp. (RDPE) and expressed it in Bacillus subtilis A311. By a two‐step pH regulation of segmented fermentation, we significantly improved the RDPE production and decreased the fermentation cost. The two‐step regulation consisted of the first step maintained the pH value at 7.0 for 24 H and the second step adjusted the pH value up to 7.5 slowly for another 24 H. Finally, the RDPE production was increased to 74 U/mL, which was about 2.5‐fold compared with the control. Our segmented fermentation strategy provides an important experimental basis for the industrial‐scale production of RDPE.